Identification and mapping of the temperature-inducible, plasmid-encoded proteins of Yersinia spp. - Bölin, I (1988)
The structural genes of the outer membrane polypeptides of Yersinia spp. (YOPs) and the V antigen of plasmid pIB1 of Yersinia pseudotuberculosis were recently cloned and mapped (A. Forsberg, I. Bölin, L. Norlander, and H. Wolf-Watz, Microb. Pathogen. 2:123-137, 1987). The corresponding genes were localized on pYV019 and pYV8081 of Yersinia pestis and Yersinia enterocolitica, respectively. No obvious differences were observed on comparison of pIB1 and pYV019, whereas pYV8081 showed intragenic as well as extragenic changes. However, one region of plasmid pYV8081, which coded for the V antigen, YOP3, and YOP4a, was essentially conserved among the three plasmids. Since this region is connected with the Ca2+ region, we suggest that the conserved region of the virulence plasmids of Yersinia spp. be extended to include both of these regions. Low amounts of the YOPs were detected in the membrane fraction at 37 degrees C in the presence of 2.5 mM calcium. Only minor differences were noticed when the individual YOPs of Y. pestis and Y. pseudotuberculosis were compared. Several differences were observed when the YOPs of Y. enterocolitica were included for comparison. All Y. enterocolitica proteins, except YOP1, YOP4b, and the V antigen, exhibited changes in their characteristic molecular sizes. Although these differences were within a range of +/- 2 kilodaltons, the isoelectric point was retained for each protein type.